Effects of intraoperative liberal fluid therapy on postoperative nausea and vomiting in children—A randomized controlled trial. Issue 8 (6th June 2017) - Ashok, Vighnesh; Bala, Indu; Bharti, Neerja; Jain, Divya; Samujh, Ram
Summary: Background: Postoperative nausea and vomiting (PONV) is one of the most distressing complications following surgery. Supplemental perioperative fluid therapy might be an effective strategy to reduce PONV in children. Objectives: The study was conducted to evaluate the effects of intraoperative liberal fluid therapy with crystalloids on PONV in children. Methods: In this randomized trial, a total of 150 children of 3‐7 years undergoing lower abdominal and penile surgery under general anesthesia were randomly assigned into two groups. "Restricted group" received 10 mL kg −1 h −1 and "Liberal group" received 30 mL kg −1 h −1 infusion of Ringer's lactate solution intraoperatively. All patients received a caudal block and intravenous paracetamol for analgesia. No opioids and muscle relaxants were used. All episodes of nausea‐vomiting and the requirement of rescue antiemetic were assessed during 24 hours postoperatively. Results: The incidence of PONV was significantly less in the liberal group patients as compared to the restricted group; 33 (45.8%) patients in the restricted group had vomiting as compared to 20 (27.4%) patients in the liberal group (RR 0.59, 95% CI: 0.38‐0.93, P =.021). The adjusted odds ratio of PONV for the liberal group vs restricted group was 2.24 (95% CI: 1.12‐4.48, P =.022). The incidence of fluid intake during the first 6 postoperative hours was significantly higher in the restricted group patients; 60 (83%) children in the restricted group complained of thirst as compared to 12 (17%) children in the liberal group (RR 0.19, 95% CI: 0.18‐0.33, P =.0001). The parents of the liberal group were more satisfied as compared to the restricted group (mean difference −0.9, 95% CI: −1.8, −0.1, P =.04). None of the children had any complication attributed to the liberal fluid therapy. Conclusion: Liberal intraoperative fluid therapy was found to be effective in reducing PONV in children undergoing lower abdominal surgery.